1996
DOI: 10.1128/jvi.70.4.2627-2631.1996
|View full text |Cite
|
Sign up to set email alerts
|

Human cytotoxic T-cell memory: long-lived responses to vaccinia virus

Abstract: Peripheral T lymphocytes can be classified into two groups: naive and memory T cells. The focus of this study was to examine the duration of T-cell memory in humans. Vaccinia virus replicates in the cytoplasm of infected cells and is not thought to persist or become latent after the acute phase of infection. We identified long-lived vaccinia virus-specific memory cytotoxic T cells in adults who had been immunized against smallpox as children. Initially, we detected vaccinia virus-specific T cells in peripheral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
55
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(66 citation statements)
references
References 28 publications
11
55
0
Order By: Relevance
“…First, the polyvalent poxvirus vaccine formulations and vaccinia vaccines also included EEV antigens and thus EEV-mediated neutralizing antibodies may play an important role for part of the protection as reported by previous studies (Appleyard et al, 1971;Boulter and Appleyard, 1973;Fogg et al, 2004;Galmiche et al, 1999;Hooper et al, 2003Hooper et al, , 2004Law and Smith, 2001). Second, cell-mediated immunity (CMI) may also be critical for protection against smallpox infection (Demkowicz et al, 1996;Ennis et al, 2002;Frey et al, 2002;Kennedy et al, 2004). The finding that the increased IMV neutralizing antibody did not correlate with increased protection will have important impact to the design of subunit-based poxvirus vaccines.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…First, the polyvalent poxvirus vaccine formulations and vaccinia vaccines also included EEV antigens and thus EEV-mediated neutralizing antibodies may play an important role for part of the protection as reported by previous studies (Appleyard et al, 1971;Boulter and Appleyard, 1973;Fogg et al, 2004;Galmiche et al, 1999;Hooper et al, 2003Hooper et al, , 2004Law and Smith, 2001). Second, cell-mediated immunity (CMI) may also be critical for protection against smallpox infection (Demkowicz et al, 1996;Ennis et al, 2002;Frey et al, 2002;Kennedy et al, 2004). The finding that the increased IMV neutralizing antibody did not correlate with increased protection will have important impact to the design of subunit-based poxvirus vaccines.…”
Section: Discussionmentioning
confidence: 90%
“…However, more studies are still needed to establish the scale-up production of these vaccines and to confirm their safety profile in larger human populations. Although vaccinia virus is a potent vaccine and has the distinct ability to produce long lasting immunity in humans (Crotty et al, 2003;Demkowicz et al, 1996), the nature of its protective antigens has just begun to be revealed (Fogg et al, 2004;Hooper et al, 2004;Pulford et al, 2004). The corresponding epitopes involved in the activation of host immune responses at the B and T cell level that lead to protective immunity are much less understood.…”
Section: Introductionmentioning
confidence: 99%
“…Mass immunization with VACV during the smallpox eradication program indicated a critical role for cellular immune responses, since severe complications could occur in patients with T cell deficiencies [31][32][33]. However very little information is available on the role of cell-mediated immunity in protective VACV vaccination, although more recent analyses suggest that humans maintain VACV specific T cells for decades after vaccination [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…The duration of humoral and cell-mediated protective immunity afforded by smallpox vaccination remains unknown, yet there is both empirical [96,97] and experimental [43,[98][99][100] evidence that some degree of immunity to smallpox persists for several decades postvaccination. In addition, Hammarlund and colleagues recently reported that smallpox vaccination as much as 48 years pre-exposure conferred immunity to humans exposed to monkeypox [101].…”
Section: Discussionmentioning
confidence: 99%